2015
DOI: 10.1002/chem.201502177
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Light and pH‐Responsive Polypyrrole@Polyacrylic acid/Fluorescent Mesoporous Silica Nanoparticles for Imaging and Chemo‐Photothermal Cancer Therapy

Abstract: We have rationally designed a new theranostic agent by coating near-infrared (NIR) light-absorbing polypyrrole (PPY) with poly(acrylic acid) (PAA), in which PAA acts as a nanoreactor and template, followed by growing small fluorescent silica nanoparticles (fSiO2 NPs) inside the PAA networks, resulting in the formation of polypyrrole@polyacrylic acid/fluorescent mesoporous silica (PPY@PAA/fmSiO2 ) core-shell NPs. Meanwhile, DOX-loaded PPY@PAA/fmSiO2 NPs as pH and NIR dual-sensitive drug delivery vehicles were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 71 publications
2
11
0
Order By: Relevance
“…To date, much effort has been made to construct multifunctional mesoporous silica nanoparticles as a platform for the synergistic therapy with chemotherapy and magnetic hyperthermia/photothermal therapy . For example, Ruiz‐Hernandez et al synthesized γ‐Fe 2 O 3 /mesoporous silica microspheres, and found that these magnetic microspheres showed the sustained drug release behavior and ability to generate heat under a low‐frequency AMF .…”
Section: Introductionmentioning
confidence: 99%
“…To date, much effort has been made to construct multifunctional mesoporous silica nanoparticles as a platform for the synergistic therapy with chemotherapy and magnetic hyperthermia/photothermal therapy . For example, Ruiz‐Hernandez et al synthesized γ‐Fe 2 O 3 /mesoporous silica microspheres, and found that these magnetic microspheres showed the sustained drug release behavior and ability to generate heat under a low‐frequency AMF .…”
Section: Introductionmentioning
confidence: 99%
“…After just 5 min exposure, the temperatures of the nonfunctionalized BG, B, and G were boosted to 39, 46, and 44 °C, respectively. PPy confers higher photothermal stability and compatibility owing to enhanced NIR absorption up to 1300 nm . These contribute to the better photothermal performance of the nanomaterial.…”
Section: Resultsmentioning
confidence: 99%
“…Photothermal performanceo fa-MoO 3À Àx Figure 5C and Ds how the temperature enhancement profiles upon exposure to the 808 nm laser.Atotal volume of 0.5 mL of nonfunctionalized and PPy-functionalized BG, B, and Gw as exposed to the laser (808 nm, 0.5 Wcm À2 ). After just 5min exposure,t he temperatures of the nonfunctionalized BG, B, and Gw ere boosted to 39, 46, and 44 8C, respectively.P Py confers higher photothermal stability and compatibility [54] owing to enhanced NIR absorption up to 1300 nm. [55] These contributet o the better photothermal performance of the nanomaterial.…”
Section: Optical Properties Of A-moo 3à àXmentioning
confidence: 99%
“…Zhang et al [121] also prepared core–shell multifunctional PPy@polyacrylic acid/fluorescent mesoporous silica nanoparticles (designated as PPY@PAA/fmSiO 2 NPs) which integrate the high drug storage capacity, NIR light and pH dual-stimuli controlled drug release property, and strong fluorescence intensity, as shown in Figure 19. Uniform PPy NPs sized about 40 nm were firstly prepared in water through the chemical oxidation polymerization method using PVA as the stabilizer.…”
Section: Multifunctional Ppy-based Therapy Platforms With Nir-trigmentioning
confidence: 99%